Feasibility of audio-visual teaching materials to support tennis learning - Septian Raibowo; Abi Fajar Fathoni; Sapto Adi (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
This study aims to produce court tennis audio-visual teaching materials and determine the effectiveness of audio-visual teaching materials to support court tennis learning. This research is development research with stages: needs analysis, data collection, product development, expert validation, product testing, product revision, and evaluation. The subjects of this study were taken using a random sampling method, amounting to 47 people. The instruments used to collect data were questionnaire sheets, expert validation sheets and further tests were analyzed using descriptive statistics. Seeing the effectiveness of the product using an experimental design with the format